Roberts's syndrome and clonidine. Issue 6 (December 1979) - Stoll, C; Levy, J M; Beshara, D
Abstract : A child is described with features of Robert's syndrome. The mother took clonidine during pregnancy. The question of a relationship between the child's abnormalities and clonidine is raised.